2020
DOI: 10.3892/ijo.2020.4983
|View full text |Cite
|
Sign up to set email alerts
|

E6‑regulated overproduction of prostaglandin�E2 may inhibit migration of dendritic cells in human papillomavirus 16‑positive cervical lesions

Abstract: Continuous human papillomavirus (HPV) infection is a critical cause of cervical lesions; however, the specific mechanism is currently not clear. E6 is one of the most important oncoproteins associated with HPV, which regulates synthases in the production of prostaglandin E2 (PGE 2 ). Notably, PGE 2 has been reported to be upregulated in cervical lesions. An insufficient number of mature dendritic cells (DCs), which is unable to cause an effective immune response, is an important cause of cervical lesions. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Several reports have suggested that PGE 2 may improve the migratory ability of dcs (8)(9)(10). On the other hand, a few studies, including our previous study, have provided contradictory results, suggesting an inhibitory role of PGE 2 in dc migration (11,12). Therefore, it remains a priority to clarify the regulatory mechanism of PGE 2 on the migratory ability of dcs.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Several reports have suggested that PGE 2 may improve the migratory ability of dcs (8)(9)(10). On the other hand, a few studies, including our previous study, have provided contradictory results, suggesting an inhibitory role of PGE 2 in dc migration (11,12). Therefore, it remains a priority to clarify the regulatory mechanism of PGE 2 on the migratory ability of dcs.…”
Section: Introductionmentioning
confidence: 69%
“…In our previous study, it was demonstrated that compared with normal cervical tissues, the expression of PGE 2 was gradually upregulated in samples of low-grade squamous intraepithelial lesion, high-grade squamous intraepithelial lesion and squamous carcinoma, which was accompanied by the progression of the disease ( 11 ). Therefore, an association between the regulation of DC migration by PGE 2 and the progression of cervical cancer was hypothesized to exist, based on the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that AKR1B1-deficient cervical cancer cell lines exhibit lower proliferation, migration, and invasion than nonmanipulated cells [ 159 ]. Concerning recent reports, AKR1B1 suppression could constrain PGE2 activity and thus disturb cervical carcinogenesis by preventing angiogenesis and cancer cell proliferation as well as inducing apoptosis [ 160 ]. Also, CD109, as a result of its role in transforming growth factor-β1 (TGF-β1) signaling and signal transducer and activator of transcription 3 (STAT3) activation, could be an innovative target for cervical cancer therapy [ 161 163 ].…”
Section: Crispr/cas9 In Cancersmentioning
confidence: 99%
“…Prostaglandin E2. Increased expression of PGE2 has been found in the immune infiltrates in HPV-mediated lesions of the cervix (Huang et al, 2020). It is secreted by both CD83+ mature DCs and MDSCs.…”
Section: Factors In the Microenvironment Of Hpv Lesions Promoting Treg Numbers And/or Functionmentioning
confidence: 99%
“…Prevention of egress of DCs may be one of the factors that add to an incompetent immune response and hence there is persistent disease and its eventuality. This altered pattern of DC distribution was paralleled by a gradual increase in the concentration of PGE2 synthases and the end product PGE2 in the tissues as the lesions evolved from LSIL to HSIL to SCC (Huang et al, 2020). Of the four receptors of PGE2, EP2 and EP4 are expressed on the surface of myeloid DCs during their complete life cycle (Scandella et al, 2002).…”
Section: Anergic Lcs In Cervical Precancer and Invasive Cancermentioning
confidence: 99%